Analisis Kontribusi Teknologi Perbankan Digital dan Biaya Corporate Social Responsibility terhadap Kinerja Keuangan Perbankan - Nusron, Lulu Amalia; Rahandhika Ivan Adyaksana; Wandan Zulvanadya Cipta Pribadi (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
The development of digital technology has brought significant changes to the banking industry, particularly through the implementation of internet banking and mobile banking services that aim to support financial inclusion. In addition, corporate concern for social aspects through corporate social responsibility (CSR) spending has also become an essential factor in ensuring business sustainability and increasing public trust. This study aims to analyze the effect of internet banking, mobile banking, and CSR expenses on the financial performance of banking institutions. The research population consisted of banking companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2022 period, with a total sample of 55 companies that met the data completeness criteria. The analysis method employed was multiple linear regression to determine the relationship and influence of the independent variables on financial performance as the dependent variable. The results show that internet banking has a significant positive effect on financial performance, indicating that the more optimal the use of internet banking services, the better the financial performance of banks. Similarly, CSR expenses also have a positive effect on financial performance, suggesting that effective and efficient allocation of CSR funds provides benefits not only for society but also for the long-term sustainability of the banks. On the other hand, mobile banking does not have a significant effect on financial performance, implying the need for improving service quality, enhancing technological features, and strengthening digital literacy so that mobile banking can contribute more effectively to banking performance. Therefore, the findings highlight the importance of digital innovation and integrated socio-economic strategies to strengthen the sustainability and competitiveness of the banking sector in Indonesia.